Adsorption of phenol by activated carbon produced from decanter cake - Asma Shufieyah, Zainal Abidin (2009)
Activated carbon from agricultural waste can be produce from various methods, either through physical activation or chemical activation. The studies involve on producing activated carbon from decanter cakes by using chemical activation method. The chemical agent use is zinc chloride as in previous research; the agent is very efficient in producing activated carbon with high surface area and large pores. The efficiencies of the activated carbon are tested with the removal capacities of organic waste such as phenol. Phenol is chosen because phenols are widely present in the industrial waste and its effect is harmful to the environment. For the preparation of activated carbon, the suitable ratio of zinc chloride to the decanter cakes is 3:5 and the effective temperature of pyrolysis are 700°C and 900°C. For the pH effect, the removal is increased as the pH increased from 2 to 6 and starts to decrease at pH of 8 until 12. Activation with zinc chloride can remove phenol more than 90% at optimum condition.